ANALISIS PENGARUH MOTIVASI KERJA, KOMPETENSI DAN BEBAN KERJA TERHADAP KINERJA PEGAWAI DENGAN DISIPLIN KERJA SEBAGAI VARIABEL MODERASI (Studi Empiris Pada Pengurus Barang Di Lingkungan Pemerintah Kota Semarang) - Dian Permatasari; Syuhada Sufian; Yanuar Rachmansyah (Magister Manajemen STIE Bank BPD Jateng, 2019)
The purpose of this study was to examine and analyze the effect of work motivation, competence and workload on the performance of employees in the Municipality of Semarang. Population in this research is 147 administrators of local property in Semarang City Government. Using the Slovin formula, 108 samples were obtained. The analysis tool in this study using the Partial Least Squares - Structural Equation Modeling with the help of software applications SmartPLS version 3.2.7. Based on the results of the study, it can be concluded that work motivation has a positive effect on employee performance, competence has a positive effect on employee performance, workload does not affect employee performance, work discipline does not affect employee performance, work discipline strengthens the influence of work motivation on employee performance, and work discipline cannot moderate the influence of competence on employee performance